Sínteses quimioenzimáticas dos fármacos (R)-luliconazol, (R)-clorprenalina e análogos e síntese química de substâncias imidazólicas - Fonseca, Thiago de Sousa (2017)
The preparation of the antifungal (R)-luliconazole (R-1) and β-agonist (R)-cloroprenaline (R-12 a) drugs and analogues (R-12 b-j) had as key step the preparation of β-halohydrins and β-haloacetates chiral, via kinetic resolution of the corresponding racemic acetates, mediated by lipase. The rac-2-chloro-1-(2,4-dichlorophenyl)ethyl acetate, rac-4 or rac-11 b was used as the "template" substrate to establish the ideal conditions for kinetic resolution via hydrolysis. Through the screening of commercial lipases, were selected the C. antarctica type B, CAL-B, immobilized on acrylic resin (Novozym 435®) and T. lanuginosus (TLL) immobilized on immobead-150, leading to the c values of 50%, e.e.s e e.e.p >92% and E of 185 and 128, respectively. Were evaluated: reaction time, temperature, enzyme/substrate ratio, pH, absence or presence of cosolvents and enzyme reuse. CAL-B was more efficient than TLL, requiring a lower enzyme/substrate ratio (0.5:1) and presenting high activity and selectivity in up to 5 cycles reactions. The best conditions for the resolution of rac-4 were the use of PO43- buffer (pH 7) in the absence of cosolvents, 15 min reaction at 45 °C, leading to c = 50%, e.e.s e e.e.p >99% and E >200. These conditions were used to resolve acetate rac-11 a, which leads to the intermediate in the synthesis of (R)-12 a as well β-haloacetates rac-11 b-j, leading to the analogous (R)-12 b-j. Adjustments in the reaction times were performed (4 h - 9 d) so that the values of c close to 50%. The esters rac-11 a-j were resolved with c ≈ 50%, values of e.e.s and e.e.p = 92 - >99% and E >200. The influence of the esters’ substituents in the time of the kinetic resolution was analyzed considering the steric and electronic effects and evoking the fitting model induced substrate-enzyme with the presence of the hydrophobic pockets. Finally, starting from (S)-2-chloro-1- (2,4-dichlorophenyl)ethanol, (S)-3, (R)-1 was obtained in 43% yield. In order to achieve an atomic economy, we converted the (S)-halohydrins (S)-10 a-j into the respective (R)-acetates (R)-11 a-j via the Mitsunobu reaction, yields ranging from 78-89%. (R)-11 a-j were transformed into the (R)-epoxides (R)-34 a-f; h-j in yields from 68-75% and (R)-11 g was transformed into (R)-halohydrin (R)-10 g in 60% yield. Subsequently, (R)-34 a-f; h-j and (R)-10 g reacted with isopropilamine, yielding (R)-12 a in 71% yield and the analogs (R)-12 b-j in yields 71-80%. Lastly, four imidazole derivatives with yields 72-90% were synthesized, and 1-phenacylimidazole (13) showed antifungal activity against phytopathogenic fungus Fusaruim sacchari, besides the anticorrosive activity for carbon steel.